Speech functions and politeness in Indonesian communication - Kun Mustain (UPT P2M Politeknik Negeri Malang, 2011)
In communication, people care for politeness in their speech so as to successfully communicate the meaning they want to express. This article starts the discussion from speech function and then goes to the one on politeness theories in communication. From the speech functions section, the writer discussion several types of speech function provided with Indonesian language examples. One of the most popular theories on the speech and communication is Gricean maxims, i.e. quantity, quality, relation, and manner maxims. Basing the discussion on this theory, the writer discusses how politeness is achieved in Indonesian language communication.